Peran Serta Masyarakat dalam Penyelenggaraan Pendidikan: Studi Kasus di SDN Pulogadung 01 Pagi - Titania Susandri; Abdullah Jawas; Ekky Kurnia Ramadhan; Fidha Nazifah; Hadana Putri Fadilah (Sahabat Akademia Group, 2026)
This study aims to analyze the forms, levels, and contributions of community participation in educational implementation at SDN Pulogadung 01, East Jakarta. A qualitative case study approach was employed. Data were collected through interviews with the school principal, document analysis, and a review of relevant literature. The findings indicate that community participation involves parents, the school committee, neighborhood organizations, alumni, and local community members in planning, implementation, monitoring, and evaluation of school programs. The dominant forms of participation include providing feedback, moral support, and social oversight. Community involvement has reached the levels of information sharing, consultation, and collaboration, but has not yet achieved empowerment, as community members have limited authority in strategic school decision-making. The study also reveals that participation is stronger during program implementation than in monitoring and evaluation activities. This article highlights that community participation should not be measured solely by attendance at school forums, but also by meaningful involvement in decision-making, monitoring, and evaluation processes. Therefore, strengthening community capacity, optimizing the role of school committees, and promoting more participatory communication are necessary to support transparent and accountable school governance.